New insights into the vertebral Hox code of archosaurs. Issue 5 (15th September 2015) - Böhmer, Christine; Rauhut, Oliver W. M.; Wörheide, Gert
SUMMARY: Variation in axial formulae (i.e., number and identity of vertebrae) is an important feature in the evolution of vertebrates. Vertebrae at different axial positions exhibit a region‐specific morphology. Key determinants for the establishment of particular vertebral shapes are the highly conserved Hox genes. Here, we analyzed Hox gene expression in the presacral vertebral column in the Nile crocodile in order to complement and extend a previous examination in the alligator and thus establish a Hox code for the axial skeleton of crocodilians in general. The newly determined expression of HoxA‐4, C‐5, B‐7, and B‐8 all revealed a crocodilian‐specific pattern. HoxA‐4 and HoxC‐5 characterize cervical morphologies and the latter furthermore is associated with the position of the forelimb relative to the axial skeleton. HoxB‐7 and HoxB‐8 map exclusively to the dorsal vertebral region. The resulting expression patterns of these two Hox genes is the first description of their exact expression in the archosaurian embryo. Our comparative analyses of the Hox code in several amniote taxa provide new evidence that evolutionary differences in the axial skeleton correspond to changes in Hox gene expression domains. We detect two general processes: (i) expansion of a Hox gene's expression domain as well as (ii) a shift of gene expression. We infer that the ancestral archosaur Hox code may have resembled that of the crocodile. In association with the evolution of morphological traits, it may have been modified to patterns that can be observed in birds.